Comparing the effects of four propagation methods on hybrid chestnut seedling quality - Taylor Evans (Elsevier, 2021)
Extensive resources have been used to breed hybrid chestnuts for reintroduction into the historical range of the American chestnut (Castanea dentata). Improving seedling quality is an efficacious method to improving restoration outcomes and nursery propagation methods can be selected to improve seedling quality, increasing the likelihood of survival. Four production methods (bed grown, air prune beds, container grown, and a multi-container method) and three media types (field soil, peat-perlite-vermiculite mix, and pine bark-rice hulls-sand mix) were compared across four measures of seedling quality (height, root collar diameter, root volume, and number of first order lateral roots) to examine their effects on seedling quality. Additional analyzes of survival and cost per seedling were conducted as well. Air prune beds performed comparably in both seedling quality and cost to standard bed grown and container grown seedlings with potential advantages over these two methods. Multi-container method seedlings underperformed compared to bed grown and container grown seedlings. A decision tree was produced to assist nurseries in selecting a propagation method most appropriate to their nursery, intended restoration site, and constraints.